Influence of waveguide strain and surface morphology on AlGaN-based deep UV laser characteristics. (3rd September 2018) - Kuhn, Christian; Martens, Martin; Mehnke, Frank; Enslin, Johannes; Schneider, Peter; Reich, Christoph; Krueger, Felix; Rass, Jens; Park, Jae Bum; Kueller, Viola; Knauer, Arne; Wernicke, Tim; et al.
Abstract: The waveguide strain and the surface morphologies of AlGaN-based laser heterostructures emitting in the deep UV spectral range have been investigated. In particular, the impact of the AlGaN heterostructure design on the strain relaxation as well as the effect of the growth temperature on the surface morphology were explored. We found strain-induced plastic relaxation for laser heterostructures with 130 nm thick Al0.45 Ga0.55 N waveguide layers, whereas pseudomorphic growth was obtained for laser heterostructures with Al0.70 Ga0.30 N waveguide layers. Optically pumped lasing near 280 nm was demonstrated for the coherently grown laser heterostructures. A strong correlation of the surface morphology with the waveguide growth conditions was also observed. Low growth temperatures of 900 °C lead to a high density of V-pits originating from dislocations. By increasing the growth temperatures to 1070 °C the V-pit density significantly decreases, resulting in a more than two-fold reduction of the threshold power density of optically pumped lasers.